A Progressive and Cell Non-Autonomous Increase in Striatal Neural Stem Cells in the Huntington's Disease R6/2 Mouse - Batista, Claudia M. C. (J Neurosci, 2006)
Neural stem and progenitor cells are located in the subependyma of the adult forebrain. An increase in adult subependymal cell proliferation is reported after various kinds of brain injury. We demonstrate an expansion of neural precursor cells in the postnatal subependyma in a murine genetic disease model of Huntington's disease (HD), the R6/2 mouse. We used the in vitro neurosphere assay as an index of the number of neural stem cells in vivo and to assess proliferation kinetics in vitro and in vivo bromodeoxyuridine labeling to assess the progenitor cell population and their fates. Disease progression in this model leads to an increase in the numbers of neural stem cells in the adult striatal subependyma. This increase is produced cell non-autonomously by events in the R6/2 brains as the mice become increasingly symptomatic. Once the neural stem cell increase is induced in vivo, it is maintained during in vitro passaging of neural stem cells, but the neural stem cell increase is not reproduced during in vitro passaging of neural stem cells from presymptomatic R6/2 mice. In addition, we show that some of the R6/2 neural progenitor cells show a change from their normal migration destiny toward the olfactory bulb. Instead, some of these cells migrate into the striatum, one of the main affected areas in HD. Our findings demonstrate that HD damage recruits precursor cells in two ways: expansion of neural stem cells and altered migration of progenitor cells.